PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MATA PELAJARAN IPAS - Suci Destriani; Pupun Nuryani; Sri Muria Rahmaniah (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This study focuses on low motivation and student learning outcomes. This study emphasizes the use of TGT (Teams Games Tournament) type cooperative learning model to improve motivation and learning outcomes of fifth grade elementary school students. The problem faced is the lack of student learning motivation so that low student learning outcomes. This study uses this learning model, there are learning steps, which include; 1) class presentation; 2) Team; 3) games; 4) tournaments; 5) Team recognition. This study uses two cycles that refer to the Kemmis and Taggart model. Data collection is carried out through observation and post-test results of students in each cycle. Based on the results of the study from each cycle, it shows an increase in student learning motivation as seen from student involvement in asking questions, discussing and completing assignments. Then the student learning outcomes show an increase. Thus, this study shows that the TGT type cooperative learning model is effective in improving student learning outcomes, as well as providing a positive impact on student motivation in the subject of science in fifth grade elementary school students.